Penentuan Batas Waktu Pewaris Yang Mafqud Era 4.0 : Studi Pandangan Hakim PA Kota Medan - Alvina Dwi Juliantika Putri; Azwani Lubis (Institut Agama Islam Negeri (IAIN) Bone, 2025)
Determining the time limit for a missing heir is a crucial issue in Islamic inheritance law and Indonesian legislation. In Islamic law, there are differing opinions among scholars regarding the waiting period for declaring a missing person deceased, ranging from four years to depending on the judge's ijtihad. Meanwhile, the Civil Code provides a provision of up to five years, while the Compilation of Islamic Law (KHI) does not explicitly regulate this, so judges play a crucial role in determining the status of missing. This research used a qualitative method with a case study approach at the Medan City Religious Court, through interviews with judges and a review of court decisions. The results show that judges determine the status of missing heirs by considering the circumstances of the disappearance, evidence, witnesses, and search efforts made by the heirs. Mafqud inheritances may not be distributed before legal certainty is achieved to protect their rights. In the era of the industrial revolution 4.0, digital technology also influences the process of determining mafqud, particularly through digital footprints, population data, and electronic evidence that can strengthen judges' considerations. However, technological advances also pose new challenges, such as the presence of digital assets in inheritances. Therefore, collaboration between Islamic law, Indonesian positive law, and the use of modern technology is necessary to ensure that the determination of mafqud status is fair, wise, and relevant to current developments.